Using Climate Data to Increase Agriculture Yields - Joyette, Antonio (Inter-American Institute for Cooperation on Agriculture (IICA), 2023)
Guest speakers: Dr. Antonio Joyette, Meteorologist, Climate & Environmental Scientist, University of the West Indies